WASTE MANAGEMENT IN NIGERIA: COMPARATIVE SOCIOLOGICAL PERSPECTIVES FROM GERMANY AND SWEDEN - Mustapha, Ahmed (African Journal of Social and Behavioural Sciences, 2025)
The significance of waste management in populated countries like Nigeria cannot be overemphasised because of its associated health, safety, environmental, land use and socioeconomic challenges. Hence, this study aims to describe the methods of waste management in Nigeria, the challenges of waste management in Nigeria, the strategies employed in waste management in Germany and Sweden, and the lessons learned from these strategies. Furthermore, this study distinguishes itself by adopting and triangulating contemporary sociological thoughts on waste management. More so, the desk review method was used in order to provide a comparative picture of waste management in Nigeria, Germany and Sweden. The study revealed that waste management in Nigeria is not in good condition due to the increasing generation of waste, inadequate funding, poor policy implementation, etc. In addition, the study established that waste management in Germany and Sweden are in better condition due to alternative source of funding, door to door system of collection, strong rules and regulations, high recycling rate etc. the study concluded that for Nigeria to have a better condition of waste management, government must ensure that waste management policies are fully implemented through prosecution of offenders involving in unlawful dumpsite, formalization of informal methods of waste management and the three arms of government and the private sector must contribute some percentage of their income to the funding of waste management.